2022
DOI: 10.1038/s42003-022-03185-3
|View full text |Cite
|
Sign up to set email alerts
|

Brain connectivity fingerprinting and behavioural prediction rest on distinct functional systems of the human connectome

Abstract: The prediction of inter-individual behavioural differences from neuroimaging data is a rapidly evolving field of research focusing on individualised methods to describe human brain organisation on the single-subject level. One method that harnesses such individual signatures is functional connectome fingerprinting, which can reliably identify individuals from large study populations. However, the precise relationship between functional signatures underlying fingerprinting and behavioural prediction remains unc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 51 publications
2
24
2
Order By: Relevance
“…Instead, our results were contingent on the inclusion of PC3 as a predictor of interest, suggesting higher-order PC deviations capturing individual variation in FC were most relevant to the visual and auditory effects of ayahuasca. Furthermore, predictive edges were found to span primarily both higher order systems (DMN, FPN) and primary systems (VIS, SM), with the former contributing more (in number) to behavioural prediction as per prior work 12,21,37 . Given their developmentally late maturation 79 , susceptibility to individual environmental effects 80 and, dense 5-HT2A expression 81 and coordination of multisensory integration in comparison to primary systems 61 , higher-order regions may more easily account for divergent phenomena, more so than primary systems, themselves partially influenced by the temporary states of each individual during scanning 82 .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Instead, our results were contingent on the inclusion of PC3 as a predictor of interest, suggesting higher-order PC deviations capturing individual variation in FC were most relevant to the visual and auditory effects of ayahuasca. Furthermore, predictive edges were found to span primarily both higher order systems (DMN, FPN) and primary systems (VIS, SM), with the former contributing more (in number) to behavioural prediction as per prior work 12,21,37 . Given their developmentally late maturation 79 , susceptibility to individual environmental effects 80 and, dense 5-HT2A expression 81 and coordination of multisensory integration in comparison to primary systems 61 , higher-order regions may more easily account for divergent phenomena, more so than primary systems, themselves partially influenced by the temporary states of each individual during scanning 82 .…”
Section: Discussionmentioning
confidence: 88%
“…While a subset of 250 edges could maximally define a subject's fingerprint, their importance markedly dropped under ayahuasca. Disseminated across higher-order association cortices these regions are shown to encode the majority of inter-individual variance 12,37 . Importantly, it has been previously hypothesised that the appearance of a desegregated functional architecture under psychedelics stems from the impairment of these same functional subsystems 35 .…”
Section: Local Shifts In Functional Connectivity Stability Drive Alte...mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the use of HACF frames with enhanced subject identifiability may amplify brain-behavior associations 24,42 . On the other hand, it has also been shown that FC-based identification and prediction may constitute conflicting goals 25,26 . Therefore, here we systematically evaluated the effect of inclusion of varying levels of functional co-fluctuations on subject identifiability and predictiveness of a range of phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, a crucial missing component in the investigation of ETS is the evaluation of individual differences at different co-fluctuation amplitudes by means of prediction of phenotypes. Previous research has shown that connectivity of brain areas that contribute most to identification accuracy do not overlap with brain areas that contribute most to prediction accuracy 25 suggesting that FC uniqueness and stability on their own do not guarantee phenotypic relevance of brain connectivity representations 26 . Furthermore, it is possible that different subsets of frames are more or less predictive of different phenotypic domains.…”
Section: Introductionmentioning
confidence: 97%